Sistem Informasi Gardu Induk dan Gardu Distribusi berbasis Web - Dadang Iskandar; Insap Santosa (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
Substation Monitoring Information System and Distribution Substation PLN is a form of information system which is used to monitor the state of the substation and distribution substation PLN with utilizing the Internet. Monitoring information displayed on a website. Information system monitoring substation is needed because the existing SCADA system has not reached the distribution substation.Needs monitoring system is used to increase the reliability of electrical equipment. Information system displays measurement results in the form of voltage, temperature, flow and cosphi obtained from sensors mounted on the transformer contained in substations and distribution sub stations. Data generated in theform of serial data which is then transmitted to the web using lan network server which is then processed so that it can be displayedon website.Online processisd one well enough that the system can display data per second even though the data obtained still contained fewer errors (phase Voltage R=0.58%, S=0.64% phase, phaseT=0,42%, current=4.7% , temperature and Cosphi=0.56% =1.63%. documentation system that can be presented inform of graphs which can be determined at the time of presentation and can be printed or downloaded in multiple file formats to facilitate the analysis of the system.